Breaking Point: Violence Against Long-Term Care Staff. (May 2019) - Brophy, James; Keith, Margaret; Hurley, Michael
Direct resident care in long-term care facilities is carried out predominantly by personal support workers and registered practical nurses, the majority of whom are women. They experience physical, verbal, and sexual violence from residents on a regular basis. To explore this widespread problem, fifty-six staff in seven communities in Ontario, Canada, were consulted. They identified such immediate causes of violence as resident fear, confusion, and agitation and such underlying causes as task-driven organization of work, understaffing, inappropriate resident placement, and inadequate time for relational care. They saw violence as symptomatic of an institution that undervalues both its staff and residents. They described how violence affects their own health and well-being—causing injuries, unaddressed emotional trauma, job dissatisfaction, and burnout. They outlined barriers to preventing violence, such as insufficient training and resources, systemic underfunding, lack of recognition of the severity and ubiquity of the phenomenon, and limited public awareness.